Labour markets, social justice and economic efficiency - Kitson, Michael; Wilkinson, Frank; Martin, Ron (2000)
In conventional economic theory, a trade-off supposedly exists between social justice and economic efficiency. In reality, market and other economic institutions are dominated by power relations, sos that the sponsorship of social justice is a productive factor. Neo-liberal economic policies, by lifting the constraints on the exercise of unequal power, increased injustice and triggered a downward economic and social spiral. Reversing this requires a revolution in economic theory and policy focused on full employment, the working of labour markets, the organisation of work, and household organisation, social provision and self-sufficiency. - Reproduced
Keywords: Social justice; Labour market